1995
DOI: 10.1128/jvi.69.4.2075-2081.1995
|View full text |Cite
|
Sign up to set email alerts
|

Virus-neutralizing antibodies of immunoglobulin G (IgG) but not of IgM or IgA isotypes can cure influenza virus pneumonia in SCID mice

Abstract: The ability of monoclonal antibodies (MAbs) to passively cure an influenza virus pneumonia in the absence of endogenous T-and B-cell responses was investigated by treating C.B-17 mice, homozygous for the severe combined immunodeficiency (SCID) mutation, with individual monoclonal antiviral antibodies 1 day after pulmonary infection with influenza virus PR8 [A/PR/8/34(H1N1)]. Less than 10% of untreated SCID mice survived the infection. By contrast, 100% of infected SCID mice that had been treated with a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(79 citation statements)
references
References 55 publications
6
72
0
1
Order By: Relevance
“…Considering the potential role of cytokine dysregulation in the pathogenesis of influenza H5N1 virus, benefits of immunomodulatory therapy could also be hypothesized. Finally, passive immunotherapy using convalescent-phase serum is believed to have conferred clinical benefit in the 1918 pandemic (140), and neutralizing monoclonal antibodies have shown therapeutic efficacy in influenza A virus infection in mice with severe combined immunodeficiency (167). Thus, passive immunotherapy also remains a possible consideration for the management of human H5N1 disease (75).…”
Section: Antiviral Treatment and Other Options For Therapymentioning
confidence: 99%
“…Considering the potential role of cytokine dysregulation in the pathogenesis of influenza H5N1 virus, benefits of immunomodulatory therapy could also be hypothesized. Finally, passive immunotherapy using convalescent-phase serum is believed to have conferred clinical benefit in the 1918 pandemic (140), and neutralizing monoclonal antibodies have shown therapeutic efficacy in influenza A virus infection in mice with severe combined immunodeficiency (167). Thus, passive immunotherapy also remains a possible consideration for the management of human H5N1 disease (75).…”
Section: Antiviral Treatment and Other Options For Therapymentioning
confidence: 99%
“…More recently, Lu et al (2006) showed that a single injection of purified F(ab ) 2 fragments derived from immunoglobulin of hyperimmunized horses protected mice against a lethal H5N1 virus challenge. A murine monoclonal antibody (mab) targeting a conserved site on the HA of H1 and H2 viruses protected mice against both agents (Okuno et al, 1994), and mabs to H1, given either intact or as Fab fragments, prevented lethal H1N1 infection in SCID mice (Mozdzanowska et al, 2003;Palladino et al, 1995). Humanized mabs also prevented death when given to mice up to 3 days after an otherwise lethal H5N1 virus challenge (Hanson et al, 2006).…”
Section: Antibody Therapiesmentioning
confidence: 99%
“…Considering the observed cytokine dysregulation in H5N1-infected animals and humans, a beneficial effect of immunomodulating agents could be hypothesized and perhaps requires further study. Finally, neutralizing monoclonal antibodies have been shown effective in treating established influenza A virus infection in mice with severe combined immunodeficiency (Palladino et al, 1995). Although mice are not men, this strategy deserves attention in the treatment of a severe illness such as influenza H5N1.…”
Section: Antiviral Treatmentmentioning
confidence: 99%